Central banks' "Green Shift" and the energy transition - Alice Eliet-Doillet; Andrea Giulio Maino (The Oxford Institute for Energy Studies, 2022)
Central banks worldwide are stepping up actions in relation to climate change and taking on an increasingly important role in supporting the energy transition. Given the prominent role that central banks play in the financial markets and in influencing financing conditions, they can act as a powerful catalyst in addressing climate change. But their involvement and the potential consequences need to be evaluated in light of the trade-offs that central banks face. In this paper, we first focus on the European Central Bank and the Bank of England, as they are among the first and more active institutions that have been implementing 'green' policies. We then turn to central banks in developing countries, which have also been active in supporting the development of local green finance markets. However, governance and country-specific risks can impair central banks' efforts, especially in developing countries where these risks remain high.
Keywords: 330; Bank of England; Central Banks; Climate Change; Energy Transition; European Central Bank; green bonds; green financing; Green Policies; Monetary Policy; Net Zero Pathways